A uniqueness criterion in the multivariate moment problem - Putinar, Mihai; Vasilescu, Florian-Horia (Mathematica Scandinavica, 2003)
A determinacy criterion for the multivariate Hamburger moment problem is derived from a recent existence by extension result, [10].